2016
DOI: 10.1089/dia.2015.0046
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Nurse-Managed Insulin Infusion Protocol

Abstract: This protocol provides adequate BG control within the clinically acceptable range of 80-199 mg/dL but not within the narrower range of 140-180 mg/dL, with a low incidence of hypoglycemia. Risk factors for hypoglycemia and barriers to protocol adherence in the cardiac surgery population should be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Compton et al (2017) found that a rate of 26.0% in reaching the target level of BG had taken 8 hr to finish. TP in this study was found efficient because it achieved a longer time of maintaining the target level of BG and a shorter time for reaching the target than the non-TP group and previous studies (Compton et al, 2017;Passarelli et al, 2016).…”
Section: Efficiency Of Tpmentioning
confidence: 49%
See 3 more Smart Citations
“…Compton et al (2017) found that a rate of 26.0% in reaching the target level of BG had taken 8 hr to finish. TP in this study was found efficient because it achieved a longer time of maintaining the target level of BG and a shorter time for reaching the target than the non-TP group and previous studies (Compton et al, 2017;Passarelli et al, 2016).…”
Section: Efficiency Of Tpmentioning
confidence: 49%
“…It is necessary to maintain target BG and prevent hypoglycaemia to determine the state of effective BG control in applying a BG control protocol (Khalaila et al., 2011; Krinsley et al., 2011; Passarelli et al., 2016). The TP group was 1.4 times more likely to reach the target level of BG than the non‐TP group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After achieving the target, hyperglycaemia represents about 17.7% of the BG measurements under the dynamic algorithm, in the same proportion as in the study of Passarelli et al [21], while the rates reported in another study ranged from 35% to 48% during the 2 nd and 3 rd days of insulin infusion [20]. Indeed, hyperglycaemia is arbitrary and not following hypoglycaemia, suggesting that sugar substitution was warranted.…”
Section: Discussionmentioning
confidence: 69%